Managing Global Growth Risks and Commodity Price Shocks : Vulnerabilities and Policy Challenges for Low-Income Countries: Vulnerabilities and Policy Challenges for Low-Income Countries - Fabrizio, Stefania (Departmental Papers; Departmental Paper ;, 2012)
As part of its work to help low-income countries manage volatility, the IMF has developed an analytical framework for assessing vulnerabilities and emerging risks that arise from changes in the external environment. This paper draws on the results of the first vulnerability exercise for low-income countries conducted by the IMF staff using this new framework. It focuses on the risks of a downturn in global growth and of further global commodity price shocks and discusses related policy challenges. Chapters review recent macroeconomic developments, including the spike in global commodity prices in early 2012; assess current risks and vulnerabilities, including how a sharp downturn in global growth and further commodity price shocks would affect low-income countries; and discuss policy challenges in the face of these risks and vulnerabilities.